Kajian Teknis Dan Finansial Interkoneksi Pembangkit Listrik Tenaga Biogas Dari Palm Oil Mill Effluent (POME) Pada Sistem 20 KV Di Kabupaten Musi Rawas - Thamrin, Nj.; Yusiana, Venny (Journal of Electrical Power Control and Automation (JEPCA), 2023)
Using renewable energy is one way to reduce global warming. Minister of Energy and Mineral Resources Regulation No. 21 of 2016 concerning Purchase of Electricity and Biogas Power. The government has supported efforts to develop electrical energy from biogas. PT Evans Lestari is an oil palm plantation company operating in Mura with a plantation area of 9,220 ha and a mill of 60 tons/hour. In order to fulfill PLN's requirements to offer electricity supply, it is necessary to carry out a technical assessment of the connection and an economic analysis. The connection of the EBT PLT to PLN's 20 kV distribution system has been regulated in Directors' Decree No. 0357.K/DIR/2014. The benefits obtained from using DG include reducing power losses and improving the voltage profile of the distribution system. Among the types of DG that are commonly used, one of them is the Bio Gas Power Plant (PTBG) fueled by liquid palm oil waste.